FACTORS INFLUENCING THE EFFECTIVENESS OF INFIRMARY IN TRANSSEXUAL OPERATION PATIENT’S ATTITUDE IN THAILAND - Yodkeeree, Sopa; Wongvanichtawee, Chalermkiat; Siriwanarangsun, Porntep; Vuthimedhi, Yuwat; Thirasirikul, Jidapa (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to study management factors of effective infirmary of transsexual operation effecting toward transsexual operation infirmary and also to suggest how to improve effective infirmary of transsexual operation patient’s attitude in Thailand. This research uses the mixed methods research. The data was collected from 360 and 10 cases of the transsexual operation patients for the quantitative and qualitative research. The questionnaire was the quantitative research tool. The statistics used for data analysis were mean, percentage, standard deviation and Chi-Square, and using in-depth interviews as a tool for qualitative research The results of this research found that: the management factors of the effective infirmary of transsexual operation such as the public policy, the organizational image, the total quality management and the marketing mix at the highest level in all aspects. The suggestions to regulate the standard of the service rate for the transsexual operation infirmary, the government should support Thailand to be the center of the transsexual operation of the world, also have the method to solve the problem of the post transsexual operation patient. The infirmary should have the own identity of organizational image, the infirmary executives should have the total quality management all times and the infirmary executives should try to get the acceptation of the patients to maintain old customers.